2017
DOI: 10.1002/iroh.201701899
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and seasonal dynamics of metalimnetic Deep Chlorophyll Maximum (DCM) in a stratified meromictic tropical lake and its implications for zooplankton community distribution

Abstract: Deep Chlorophyll Maxima (DCM) is an important feature of stratified lakes and oceans but very little is known about the phenomenon in tropical systems. Proximate factors accounting for DCM presence include light, thermal stratification and nutrients but biotic interactions such as zooplankton grazing can actively support DCM formation, structure and maintenance. We examined DCM characteristics in tropical Lake Bosumtwi at biweekly intervals between April and July of 2005 and 2006 and also assessed zooplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Based on their 13 C experiment Wilkinson et al (2014) inferred that the DCL contributed only minimally to the crustacean zooplankton diet, and Sanful et al (2017) studying natural populations, reached a similar conclusion. However, Francis et al (2011), using natural-abundance isotopic analyses, concluded that the DCL was a very important food source in oligotrophic lakes.…”
Section: Discussionmentioning
confidence: 86%
“…Based on their 13 C experiment Wilkinson et al (2014) inferred that the DCL contributed only minimally to the crustacean zooplankton diet, and Sanful et al (2017) studying natural populations, reached a similar conclusion. However, Francis et al (2011), using natural-abundance isotopic analyses, concluded that the DCL was a very important food source in oligotrophic lakes.…”
Section: Discussionmentioning
confidence: 86%
“…(2017) conducted a field study on Lake Ontario and determined significant dependencies of DCM magnitude and location on the temperature profile of a lake; Sanful et al. (2017) demonstrated euphotic depth was the primary driver of DCM formation and maintenance in another field study. Somavilla et al.…”
Section: Introductionmentioning
confidence: 99%
“…Huisman et al (2006) demonstrated through numerical simulations that there exists a minimum turbulence level in the surface layer of the ocean in order to achieve a stable DCM. Scofield et al (2017) conducted a field study on Lake Ontario and determined significant dependencies of DCM magnitude and location on the temperature profile of a lake; Sanful et al (2017) demonstrated euphotic depth was the primary driver of DCM formation and maintenance in another field study. Somavilla et al (2019) connected deep chlorophyll phenomena to surface blooms in an oceanic environment: field data demonstrated that cyanobacterial biomass was prevalent below the diurnal mixed layer, toward a DCL, when the net heat flux at the water surface became positive on a seasonal timescale.…”
mentioning
confidence: 99%
“…Physical (light availability and mixing dynamics), chemical (nutrient supply), and biological (microbial food web and grazing rates) factors contribute to regulating the nature and variations of the SCM in lakes (Abbott et al, 1984;Cullen, 2015;Leach et al, 2018;Sanful et al, 2017;Sommer et al, 2012). Water clarity and underwater light are regarded as the overarching drivers of SCM variation (Hamilton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%